Performance of electrochemical amperometric sensor based on annealed and non-annealed PANI-Ag-Pt nanocomposite thin films for E. coli detection - Abdullah, Huda; Mohammad Naim, Norshafadzila; Abdul Hamid, Aidil; Mohamad Zin, Noraziah; Othman, Mohd Hafiz Dzarfan; Fen, Yap Wing; Yuliarto, Brian (Universiti Malaysia Perlis, 2025)
Herein, we report the fabrication of polyaniline with Ag-Pt alloy nanocomposite thin films based amperometric E. coli sensor. The effects of annealing at 300oC during the synthesis of PANI-Ag-Pt nanocomposite thin films are studied. XRD, AFM, FESEM and FTIR spectroscopy analyses are conducted to characterize the films. Sensor performance is investigated by the I-V characteristic of PANI-Ag-Pt films with and without the presence of E. coli. From XRD analysis, annealed films have larger crystallite sizes than non-annealed films. AFM results indicate that annealed films have lower surface roughness but larger grain size than non-annealed films. FESEM images show Ag-Pt nanorods with sizes of 200-300 nm for non-annealed films and Ag-Pt nanocubes with sizes around 100-550 nm for annealed films. The composition of PANI-Ag0.2-Pt0.8 nanocomposite thin film has higher conductivity and performed the maximum sensitivity upon E. coli presence. The sensitivity of annealed PANI-Ag-Pt films is higher than non-annealed PANI-Ag-Pt films.